Acute and delayed effects of strength training in ball velocity and accuracy in young competition tennis players - Terraza-Rebollo, M.; Baiget, E. (PLOS ONE, 2021)
This study aimed to investigate the acute and delayed effects of medicine ball throws and resistance training in ball velocity and accuracy of serve, forehand and backhand in young competition tennis players. A crossover-randomized design was used with 10 competition tennis players (6 girls and 4 boys between 14 and 18 years old). The subjects performed 6 stroke test sessions, 3 for each strength protocol. The velocity and accuracy of strokes were measured before (basal situation), 3 minutes, 24 and 48 hours after the protocol. Medicine ball throws protocol was performed by accomplishing 3 sets of 6 repetitions using a 2 kg ball, throwing it at maximal speed. Resistance training protocol was performed by accomplishing 3 sets of 6 repetitions at 75% one-repetition maximum, lifting the load at maximal speed of bench press, dead lift, one hand row and half squat. There were no significant (p > 0.05) differences in all strokes, regarding ball velocity and accuracy after each method and each recovery time, compared to the basal situation. These results suggest that medicine ball throws and resistance training methods have no acute and delayed detrimental effects on stroke velocity and accuracy in young competition tennis players.